ANTHROPOGENIC TRANSFORMATIONS OF THE MARMARIK RIVER VALLEY RELIEF AND EVOLUTION OF SECONDARY TECHNOGENIC GEOMORPHOLOGICAL PROCESSES (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
It is marked that landslides of various sizes and activity are widely spread on the southern slope of the Marmarik River valley. Bringing in exploitation of Marmarik reservoir will provoke forming and evolution of secondary technogenic geomorphological processes, which will reveal itself in the form of landslides or activization of already available landslides on its banks. The southern slope of the reservoir opposite the Tsahkamarg river mouth and convex slope a little above the dam, steeply moving to water are the most dangerous areas of landslide appearance displacements. It is offered to carry out detailed geomorphological and tacheometric investigations for well-founded forecast of dam banks treatment.
Keywords: Marmarik River; secondary technogenic processes; landslides; dam